The Staphylococcus aureus protein Sbi acts as a complement inhibitor and forms a tripartite complex with host complement Factor H and C3b. - Katrin Haupt (Public Library of Science (PLoS), 2008)
The Gram-positive bacterium Staphylococcus aureus, similar to other pathogens, binds human complement regulators Factor H and Factor H related protein 1 (FHR-1) from human serum. Here we identify the secreted protein Sbi (Staphylococcus aureus binder of IgG) as a ligand that interacts with Factor H by a-to our knowledge-new type of interaction. Factor H binds to Sbi in combination with C3b or C3d, and forms tripartite SbiratioC3ratioFactor H complexes. Apparently, the type of C3 influences the stability of the complex; surface plasmon resonance studies revealed a higher stability of C3d complexed to Sbi, as compared to C3b or C3. As part of this tripartite complex, Factor H is functionally active and displays complement regulatory activity. Sbi, by recruiting Factor H and C3b, acts as a potent complement inhibitor, and inhibits alternative pathway-mediated lyses of rabbit erythrocytes by human serum and sera of other species. Thus, Sbi is a multifunctional bacterial protein, which binds host complement components Factor H and C3 as well as IgG and beta(2)-glycoprotein I and interferes with innate immune recognition.